Pengaruh Mobilisasi Dini Terhadap Intensitas Nyeri Dan Waktu Pemulihan Fungsional (Studi Pada Pasien Post Sectio Caesarea) - Dwiharini Puspitaningsih; Anndy Prastya; Eka Diah Kartiningrum; Novitasari (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Cesarean section was a surgical procedure that was commonly associated with postoperative pain, which could limit physical movement and delay functional recovery in mothers. Pain experienced after surgery often led to fear of mobilization, resulting in prolonged bed rest and delayed return to daily activities. One non-pharmacological intervention that could be applied to manage postoperative pain and enhance recovery was early mobilization. Early mobilization was believed to reduce pain intensity and accelerate functional recovery by improving blood circulation, reducing inflammation, and stimulating physical activity. This study aimed to analyze the effect of early mobilization on pain intensity and functional recovery time in post-cesarean section patients. A quasi-experimental design with a time-series approach was used. The sample consisted of 34 respondents selected using simple random sampling, divided into an intervention group (n=17) and a control group (n=17). Data were collected using the Numeric Rating Scale (NRS) to assess pain intensity and an observation sheet to measure functional recovery time. Data were analyzed using the Friedman test and Mann-Whitney test. The results showed that before the intervention, all respondents in both groups experienced severe pain. After early mobilization, all respondents in the intervention group reported mild pain, while most respondents in the control group (82.4%) still experienced moderate pain. In terms of functional recovery, all respondents in the intervention group recovered within 24 hours, whereas the majority of the control group (52.9%) required 48 hours. Statistical analysis showed significant results (p=0.000 for pain intensity and p=0.001 for functional recovery time). In conclusion, early mobilization had a significant effect on reducing pain intensity and accelerating functional recovery in post-cesarean section patients.